Religion in a Japanese Cultural Perspective - Fatonah (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2021)
Abstract: This research was a qualitative research with descriptive phenomenological approaches and library study. Phenomenological perspective in this research was used to describe religious phenomena in the Japanese society perspective and to see further about the behavior, motivation, actions that is done by Japanese students in interpreting religion in a cultural perspective. This study also aimed to understand the characteristics of the Japanese society in interpreting religion and culture. The focus of this research was an understanding of Japanese society way of life in interpreting religion and culture. The results of this study showed that the true religion in Japan was understood and lived with lightly, not binding. Almost all religious activities in Japan rely on the idea of ​​genze riyaku. It doesn't matter Buddha or Shinto. It is not different than treating other dimensions of material life.